Network‐based rTMS to modulate working memory: The difficult choice of effective parameters for online interventions. Issue 11 (15th October 2021) - Beynel, Lysianne; Dannhauer, Moritz; Palmer, Hannah; Hilbig, Susan A.; Crowell, Courtney A.; Wang, Joyce E‐H.; Michael, Andrew M.; Wood, Eleanor A.; Luber, Bruce; Lisanby, Sarah H.; Peterchev, Angel V.; Cabeza, Roberto; et al.
Abstract: Background: Online repetitive transcranialmagnetic stimulation (rTMS) has been shown to modulate working memory (WM) performance in a site‐specific manner, with behavioral improvements due to stimulation of the dorsolateral prefrontal cortex (DLPFC), and impairment from stimulation to the lateral parietal cortex (LPC). Neurobehavioral studies have demonstrated that subprocesses of WM allowing for the maintenance and manipulation of information in the mind involve unique cortical networks. Despite promising evidence of modulatory effects of rTMS on WM, no studies have yet demonstrated distinct modulatory control of these two subprocesses. The current study therefore sought to explore this possibility through site‐specific stimulation during an online task invoking both skills. Methods: Twenty‐nine subjects completed a 4‐day protocol, in which active or sham 5Hz rTMS was applied over the DLPFC and LPC in separate blocks of trials while participants performed tasks that required either maintenance alone, or both maintenance and manipulation (alphabetization) of information. Stimulation targets were defined individually based on fMRI activation and structural network properties. Stimulation amplitude was adjusted using electric field modeling to equate induced current in the target region across participants. Results: Despite the use of advanced techniques, no significant differences or interactions between active and sham stimulation were found. Exploratory analyses testing stimulation amplitude, fMRI activation, and modal controllability showed nonsignificant but interesting trends with rTMS effects. Conclusion: While this study did not reveal any significant behavioral changes in WM, the results may point to parameters that contribute to positive effects, such as stimulation amplitude and functional activation. Abstract : Working memory is a crucial a cognitive ability that declines rapidly with aging. Repetitive transcranial magnetic stimulation (rTMS) has been proposed as an approach to enhance working memory abilities, however effects are often modest. In this study, advanced techniques were used (fMRI, network controllability and electric field modeling) to optimize rTMS effects. However, no significant differences were found between active and sham rTMS, as such the manuscript provides a detailed account of how stimulation and task parameters may have led to the lack of significant rTMS results.